Getting back to basics: Reintroduction of pelvic anatomy concepts for obstetrics and gynaecology residents. (March 2021) - Vallabhajosyula, Ranganath; Mathur, Manisha; Kathirvel, Rajeswari; Madan, Aggarwal Ieera; Kang, Julian; Mogali, Sreenivasulu Reddy
Background: A sound understanding of pelvic anatomy is essential for training in obstetrics and gynaecology (OBGYN) and for practising in the field post-qualification. There is a growing concern that surgery residents have an inadequate knowledge of anatomy and little confidence in their approach to the subject. Objective: This study aims to explain the use of an anatomy workshop to deliver a unique and self-designed innovative instruction method that employs cutting-edge resources to enhance OBGYN residents' comprehension of clinical anatomy and to discuss why this approach works. Methodology: The workshop emphasised the clinical and surgical anatomy of the female pelvis using 3-D virtual dissections, relevant plastinated specimens and also bony pelvic models that had been developed in house. Anatomists and OBGYN consultants facilitated the workshop. The students' knowledge of anatomy and their perceptions of the subject were evaluated by pre- and post-tests and a five-point Likert scale, respectively. A mixed methods analysis was applied. Results: Of the 42 participants, 26 (61.9%) completed both the pre- and post-test. The overall difference (mean percentage) between the pre- and post-test performance was 25.41%. There was a significant difference in the residents' knowledge of anatomy between the pre- and post-workshop ( p <0.05). Participants ( n =10) provided positive feedback on the workshop content, teaching tools, learning activities and educators. They recommended that the workshop should be held at least once a year (70%), and particularly during the first year of residency (90%). Conclusion: The active learning workshop enabled by multidisciplinary teaching and the innovative tools employed resulted in improved outcomes in knowledge of anatomy, confidence and learning satisfaction. Reintroduction of anatomy concepts during OBGYN residency training is needed to improve surgical training and patient care.